Analisis Kekuatan Struktur Atas Jalan Layang terhadap Beban Gempa (Studi Kasus: 6 Ruas Tol Dalam Kota Jakarta Tahap 1 Seksi A) - Ridwan, Aini Maryam; Fauzan, Muhammad; Mentari, Sekar (Jurnal Teknik Sipil dan Lingkungan, 2020)
The high potential earthquake in Indonesia made the earthquake an important factor in the planning of a building. The study aims to do the way of modeling, analyzing the inner style, displacement occurring in the current earthquake structure and knowing the vibration period and the stiffness of the structure. Research conducted in Kelapa Gading North Jakarta. Research using secondary data obtained from KSO Jaya Konstruksi-Adhikarya by using CSI Bridge. The flyover modeling is based on secondary data. The results show that 12 vibration modes may occur in the flyover structure. The largest period occurred in mode 1 that was equal to 0.84 sec which represented the behavior of the structure so that the total stiffness value of the structure was 275512.95 kN/m. Structures can be categorized as a flexible structure. Displacement is the structure of 92.5 mm and is still below the value of allowable displacement so it could be classified as the safe category. The force that occurs in the structure of the axial force, shear force, torsion, and flexure moment. Keywords: CSI Bridge, displacement, earthquake, flyover, force.